Analysis of the Reactivity of Aspirin and Clopidogrel and Its Influencing Factors in Patients with Coronary Heart Disease at High Altitude. (31st October 2021) - Chang, Rong; Wu, Jinchun; Zhang, Xiaofei; Ye, Yi; Zhou, Wenqin; Liu, Yanmin
Abstract : Objective . To evaluate the efficacy of dual-antiplatelet treatment (DAPT) in patients with coronary heart disease (CHD) at high altitude by using thrombelastogram (TEG) and to analyze the related biochemical factors affecting drug reactivity. Methods . Totally 118 CHD patients who admitted to the Qinghai People's Hospital from September 2019 to September 2020 were enrolled in the group. Those people have lived in Qinghai for a long time. Seven days after DAPT, venous blood was collected on an empty stomach in the early morning of the next day; blood routine, coagulation function, and biochemical items were tested. Thrombelastogram (TEG) was used to draw curves to calculate platelet, coagulation and fibrinolysis functions, and drug inhibition rate. Patients were divided into the aspirin resistance (AR) group, clopidogrel resistance (CR) group, dual-antiplatelet drug resistance (DAR) group, and drug-sensitive group according to different inhibition rates. The drug efficacy was analyzed, and the clinical data, biochemical indexes, and TEG parameters of each group were compared to identify the risk factors of drug resistance. Results . Those 118 CHD patients at high altitude were incorporated into the study, ranging from 38 to 84 years of age, including 81 males (68.64%) and 37 females (31.36%). The platelet function and coagulation-fibrinolysis function were detected by TEG, and MATHROMBI, MAADP, and MAAA were higher than the reference range. There were 82 cases (69.49%) of drug resistance, 36 cases (32.53%) of drug sensitivity, 17 cases (14.41%) of AR alone, and 16 cases (12.71%) of CR alone. There was no significant difference in age, gender, BMI, oxygen saturation, TG, GFR, and history of diabetes and hypertension between ACS and CCS groups (P > 0.05 ). PLT and FIB in the ACS group were higher than those in the CCS group, and the difference was statistically significant (P < 0.05 ). In addition, MATHROMBIN, MAFIBRIN, E, A, A30, and coagulation composite index were also higher than those in the CCS group, with a statistically significant difference (P < 0.05 ). Univariate analysis and logistic regression analysis suggested that age, HbA1c, FBG, and diabetes were the main factors of drug resistance. Conclusion . Antiplatelet drugs aspirin and clopidogrel resistance are associated with increased age, elevated HbA1c and FBG, and diabetes. Therefore, it is necessary to take reasonable treatment measures based on the actual situation of patients.